Bluetooth activated DC motor - Lucella, Jack (2009)
Nowadays, Bluetooth is a common way to connect and transfer information between things such as cell phones, laptops and PCs, printers, and digital cameras. The idea of using Bluetooth technology also a big motivation as it is interested in obtaining a much more comprehensive understanding of how it works. The goal of this project is to design a controller that will be able to run a DC motor wirelessly using Bluetooth technology. This controller will be able to function through a software application on a laptop or desktop computer from within a distance of the motor. This project involved three main parts to be developed, which are hardware, circuit and software. The hardware parts consists the materials that are used to build. The circuit part consists of the microcontroller circuit, because the microcontroller is known as a brain of the circuit. All the movement will be assigned by using microcontroller. The software part is to design the programming that will be used to assign an angle of movement for each DC motor.